2015
DOI: 10.3171/2015.3.peds14544
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and factors associated with infant abusive head trauma in the US

Abstract: OBJECT Head trauma is the leading cause of death in abused children, particularly prior to the age of 2 years. An awareness of factors associated with this condition as well as with a higher risk of mortality is important to improve outcomes and prevent the occurrence of these events. The objective of this study was to evaluate outcomes and factors associated with poor outcomes in infants with diagnosed abusive head trauma (AHT). Patient characteristics, socioeconomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 30 publications
5
39
1
1
Order By: Relevance
“…AHT victims have been consistently reported in the literature to be younger than children with accidental TBI (2327), which our study confirmed. In contrast to most AHT cohorts, we found a female predominance in the population of AHT (3, 15, 16, 23, 24, 2830). We found one other study that showed a female predominance in AHT (31).…”
Section: Discussioncontrasting
confidence: 95%
“…AHT victims have been consistently reported in the literature to be younger than children with accidental TBI (2327), which our study confirmed. In contrast to most AHT cohorts, we found a female predominance in the population of AHT (3, 15, 16, 23, 24, 2830). We found one other study that showed a female predominance in AHT (31).…”
Section: Discussioncontrasting
confidence: 95%
“…Characteristics associated with the accident (odds ratio) (Fig. 1) 31 Comparison of age distribution of abusive head trauma (AHT) cases between our study and a study carried out in the USA 45) . Two peaks in the number of patients were observed in the AHT group, one at approximately 1-2 months and the other at 6-8 months.…”
Section: Characteristics Associated With Aht (Odds Ratio)mentioning
confidence: 92%
“…The clinical presentations included age, sex, initial Glasgow Coma Scale, seizures (pre‐admission), vomiting (pre‐admission), bruising other than on the head, scalp findings (scalp hematoma or head bruising), long bone or rib fractures, retinal hemorrhage, neurological sequelae, and in‐hospital death. Furthermore, we compared age distribution of AHT cases <1 year of age between the AHT group in our study and AHT cases reported in the USA . We also assessed CT findings of skull fractures, SDH and its location, epidural hematoma, subarachnoid hemorrhage, and cerebral edema.…”
Section: Methodsmentioning
confidence: 99%